Co-production as an approach to developing stakeholder partnerships to reduce mental health inequalities: an evaluation of a pilot service. Issue 1 (2nd May 2016) - Lwembe, Saumu; Green, Stuart A.; Chigwende, Jennifer; Ojwang, Tom; Dennis, Ruth
Abstract : Aim: This study aimed to evaluate a pilot cross-sector initiative – bringing together public health, a community group, primary mental health teams and patients – in using co-production approaches to deliver a mental health service to meet the needs of the black and minority ethnic communities. Background: Black and minority ethnic communities continue to face inequalities in mental health service access and provision. They are under-represented in low-level interventions as they are less likely to be referred, and more likely to disengage from mainstream mental health services. Effective models that lead to improved access and better outcomes are yet to be established. It has long been recognised that to be effective, services need to be more culturally competent, which may be achieved through a co-production approach. Methods: This study aimed to evaluate the role of co-production in the development of a novel community mental health service for black and minority ethnic service users. Qualitative research methods, including semi-structured interviews and focus groups, were used to collect data to examine the use of co-production methods in designing and delivering an improved mental health service. Findings: Twenty-five patients enrolled into the study; of these, 10 were signposted for more intensive psychological support. A 75% retention rate was recorded (higher than is generally the case for black and minority ethnic service users). Early indications are that the project has helped overcome barriers to accessing mental health services. Although small scale, this study highlights an alternative model that, if explored and developed further, could lead to delivery of patient-centred services to improve access and patient experience within mental health services, particularly for black and minority ethnic communities.